THE ECONOMIC NATURE OF TAX PROFIT (INCOME) AS THE FACTOR OF ECONOMIC POLITICS OF THE STATE - V. Dubkova (Вестник Северо-Кавказского федерального университета, 2022)
It is considered the results of research the problem of improvement of enterprise profit taxation and the ways of its solution. It is considered the economic nature of tax profit with economic nature of object of taxation. As its object of taxation it is considered the surplus value, average profit, gross income. The definition of tax profit in an economic category and the algorithm for calculating the profits tax rate are offered. Value increase of labor productivity in increase the taxable profit is proved. Stimulation of action the factors ofproduction efficiency on the basis of the profit taxation are offered. On the basis of research the economic nature of tax profit decision the problem of improvement efficiency of economy and efficiency enterprise proit taxation, rice the income proit of budget and consolidate the inancial basis of municipal bodies are offered. The results of research is make the methodology basis of working out of more effective mechanism of the taxation profit of enterprises, which specially is necessary when realization of anti-crisis economic politics.